Impact of Hfq on Global Gene Expression and Virulence in Klebsiella pneumoniae - Chiang, Ming-Ko (Public Library of Science, 2011)

(untitled)
Klebsiella pneumoniae is responsible for a wide range of clinical symptoms. How this bacterium adapts itself to ever-changing host milieu is still a mystery. Recently, small non-coding RNAs (sRNAs) have received considerable attention for their functions in fine-tuning gene expression at a post-transcriptional level to promote bacterial adaptation. Here we demonstrate that Hfq, an RNA-binding protein, which facilitates interactions between sRNAs and their mRNA targets, is critical for K. pneumoniae virulence. A K. pneumoniae mutant lacking hfq (Δhfq) failed to disseminate into extra-intestinal organs and was attenuated on induction of a systemic infection in a mouse model. The absence of Hfq was associated with alteration in composition of envelope proteins, increased production of capsular polysaccharides, and decreased resistance to H(2)O(2), heat shock, and UV irradiation. Microarray-based transcriptome analyses revealed that 897 genes involved in numerous cellular processes were deregulated in the Δhfq strain. Interestingly, Hfq appeared to govern expression of many genes indirectly by affecting sigma factor RpoS and RpoE, since 19.5% (175/897) and 17.3% (155/897) of Hfq-dependent genes belong to the RpoE- and RpoS-regulon, respectively. These results indicate that Hfq regulates global gene expression at multiple levels to modulate the physiological fitness and virulence potential of K. pneumoniae.